Genomic introgression through interspecific hybridization counteracts genetic bottleneck during soybean domestication - Xutong Wang; Liyang Chen; Jianxin Ma (Genome Biology, 2019)
Abstract Background Evidence of introgression, the transfer of genetic material, between crops and their wild relatives through spontaneous hybridization and subsequent backcrossing has been documented; however, the evolutionary patterns and consequences of introgression and its influence on the processes of crop domestication and varietal diversification are poorly understood. Results We investigate the genomic landscape and evolution of putative crop-wild-relative introgression by analyzing the nuclear and chloroplast genomes from a panel of wild (Glycine soja) and domesticated (Glycine max) soybeans. Our data suggest that naturally occurring introgression between wild and domesticated soybeans was widespread and that introgressed variation in both wild and domesticated soybeans was selected against throughout the genomes and preferentially removed from the genomic regions underlying selective sweeps and domestication quantitative trait locus (QTL). In both taxa, putative introgression was preferentially retained in recombination-repressed pericentromeric regions that exhibit lower gene densities, reflecting potential roles of recombination in purging introgression. Despite extensive removal of introgressed variation by recurrent selection for domestication-related QTL and associated genomic regions, spontaneous interspecific hybridization during soybean domestication appear to have contributed to a rapid varietal diversification with high levels of genetic diversity and asymmetric evolution between the nuclear and chloroplast genomes. Conclusions This work reveals the evolutionary forces, patterns, and consequences of putative genomic introgression between crops and their wild relatives, and the effects of introgression on the processes of crop domestication and varietal diversification. We envision that interspecific introgression serves as an important mechanism for counteracting the reduction of genetic diversity in domesticated crops, particularly the ones under single domestication.